Social, family, biological and academic impact of the oppositional defiant disorder - Nathalia Andrea Castro; Jhoana Marcela López Ruiz; Diana Marisol Henao Arias; Nataly Buitrago Puerta; José Luis Camacho Franco; Juan Diego Betancur (Senderos Pedagogicos, 2014)
This article arises as a result of the research conducted on the knowledge of the causes, effects and behaviors deepen the understanding of the causes, effects and behaviors that the individual acquires to suffer Disorder Opposing Challenging (DOC), which is diagnosed incorrectly, since it gives no follow a protocol level Neuropsychological. The DOC treatment must be based on psychological interventions; which the family and the school on the characteristics of the disorder. Orient the intervention should be complemented with the use of drugs. A wrong treatment leads to develop conduct disorder in adolescence. (Rigau, García, Artigas, 2006). DOC introduces comorbidity with other disorders for this the importance of investigating aspects of family structure or the context in which the individual is located, to obtain a proper diagnosis or the cause of the triggering of such disorder.